Exploring the Lenses© Framework: regenerative design for the built environment - Greenwell, Craig Russell, author; Makela, Carole, advisor; Bohren, Lenora, committee member; Kaminski, Karen, committee member; Timpson, William, committee member (Colorado State University. Libraries, 2020)
The Living Environment Natural, Social, and Economic Systems (LENSES©) Framework is a process-based decision support tool promoting regenerative built environment design, surpassing current sustainability tools. Regenerative design is important because it restores ecosystems to pre-built environment levels. A constant comparative analysis reduced obscurity for regenerative criteria on eleven content specific Flow--Land Use, Transportation, Money, Energy, Water, Materials, Education, Ecosystems, Well-Being, Culture, and Beauty-- producing more concrete realities. A 2013 pilot study better informed the method of inquiry and coding scheme, after it was found that criteria were too broad, and findings could not be replicated using three-step coding without first delineating criteria into subjective or prescriptive topics. In this analysis, the first coding step delineated criteria into major topics, which were then refined into respective industry roles and tangible, usable design realities. Findings yielded two types of realities, subjective (i.e., Education, Money, Well-Being, Culture, and Beauty) and prescriptive (i.e., Land Use, Transportation, Energy, Water, Materials, and Ecosystems). Lessening obscurity of criteria reduced the need for facilitators to implement and use the tool, permitting stakeholders to self-guide regenerative design. Limitations of realities prevented the presentation of precision standards. Parameters for subjective realities should be established, as should standards for prescriptive realities. Designs can be regenerative following yielded realities presuming local building codes allow them and stakeholders desire to do so.
Keywords: design; processes; sustainable; framework; built environment; regenerative